The relative magnitude of transgene-specific adaptive immune responses induced by human and chimpanzee adenovirus vectors differs between laboratory animals and a target species. - Dicks, M; Guzman, E; Spencer, A; Gilbert, S; Charleston, B; Hill, A; Cottingham, M (Elsevier, 2015)
Adenovirus vaccine vectors generated from new viral serotypes are routinely screened in pre-clinical laboratory animal models to identify the most immunogenic and efficacious candidates for further evaluation in clinical human and veterinary settings. Here, we show that studies in a laboratory species do not necessarily predict the hierarchy of vector performance in other mammals. In mice, after intramuscular immunization, HAdV-5 (Human adenovirus C) based vectors elicited cellular and humoral adaptive responses of higher magnitudes compared to the chimpanzee adenovirus vectors ChAdOx1 and AdC68 from species Human adenovirus E. After HAdV-5 vaccination, transgene specific IFN-γ(+) CD8(+) T cell responses reached peak magnitude later than after ChAdOx1 and AdC68 vaccination, and exhibited a slower contraction to a memory phenotype. In cattle, cellular and humoral immune responses were at least equivalent, if not higher, in magnitude after ChAdOx1 vaccination compared to HAdV-5. Though we have not tested protective efficacy in a disease model, these findings have important implications for the selection of candidate vectors for further evaluation. We propose that vaccines based on ChAdOx1 or other Human adenovirus E serotypes could be at least as immunogenic as current licensed bovine vaccines based on HAdV-5.